2020
DOI: 10.1101/2020.10.05.20207324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linked surveillance and genetic data uncovers programmatically relevant geographic scale of Guinea worm transmission in Chad

Abstract: Background Guinea worm (Dracunculus medinensis) was detected in Chad in 2010 after a supposed ten year absence, posing a challenge to the global eradication effort. Initiation of a village-based surveillance system in 2012 revealed a substantial number of dogs infected with Guinea worm, raising questions about paratenic hosts and cross-species transmission. Methodology/Principal Findings We coupled genomic and surveillance data from 2012-2018 cases to investigate the modes of transmission between hosts and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Innovative efforts have also integrated complementary data from mobile-phone data and travel surveys with malaria parasite genetics [17]. In this work, we demonstrate that malaria parasite genetic data can identify connectivity at a small geographic scale; we utilize spatial models of human movement that have been shown, for various pathogens, to be effective for characterizing genetic linkages [30, 31]. The modeling investigation in this article leads to a better understanding of the levels, trends, and connectivity of malaria in Thiès, Senegal, and can inform decision-making for interventions in local settings.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative efforts have also integrated complementary data from mobile-phone data and travel surveys with malaria parasite genetics [17]. In this work, we demonstrate that malaria parasite genetic data can identify connectivity at a small geographic scale; we utilize spatial models of human movement that have been shown, for various pathogens, to be effective for characterizing genetic linkages [30, 31]. The modeling investigation in this article leads to a better understanding of the levels, trends, and connectivity of malaria in Thiès, Senegal, and can inform decision-making for interventions in local settings.…”
Section: Introductionmentioning
confidence: 99%
“…Adding routine genetic analysis of Guinea worms to ongoing active surveillance, case containment, and case investigation seems the best way forward in South Sudan as research in Chad has shown. 21 With a ratio of more than 60:1 infected domestic dogs to human cases in 2018-2021, dogs have clearly been driving Guinea worm transmission in Chad, where the riverine endemic area resembles Mali's, over the past decade, with incidental infection of humans. The similar 33% and 48% reductions in Guinea worm transmission to humans and dogs in Chad in 1 year (2021) may suggest parallel modes of transmission to humans and dogs by ingestion of infected transport hosts like fish rather than paratenic hosts such as frogs.…”
Section: Discussionmentioning
confidence: 99%